A revised financial satellite model for COSMO - Paul Egan; Kieran McQuinn; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2022)
This working paper provides an updated overview of the financial block satellite model in COSMO. This block allows for an analysis of macrofinancial relationships and links these back into the main COSMO specification. The critical importance of appropriately assessing macro-financial linkages in any assessment of macroeconomic stability and financial resilience has been clearly demonstrated by the global financial crisis in 2007. In light of this, considerable work has been done since the crisis to update macroeconomic models to take account of financial channels and assess financial stability risks. This update to the suite of macro-financial linkages in COSMO revisits equations for financial distress (mortgage arrears and firm insolvencies), mortgage, consumer and non-financial credit, house prices and housing supply. A new exogenous policy variable related to regulatory bank capital is also incorporated. The paper provides updated equations and estimations of long and short run relationships. It also provides an overview of the linkages with COSMO and provides an illustration of how a shock to the banking sector capital ratio propagates through the satellite model and the broader macroeconomic model.
Keywords: 330; COSMO; Mortgage Credit; Macro-prudential Regulation; Financial Distress